Assessing the Professional Standing of IT Specialists in the Polish Financial Sector. A Report from a Qualitative Study - Mecina, Jacek; Potocki, Przemysław; Niedziela, Michał (Warsaw Forum of Economic Sociology, 2019)
This study had two basic goals: (1) to identify challenges facing the financial sector over the next 3−5 years, due to changes in its environment; (2) to set out the directions for the development of the sector’s human resources. The research was focused on three thematic areas: recruitment criteria, working conditions, prospects for professional development. Five in-depth interviews with IT specialists working for banking cooperatives and for entities from the insurance market were conducted. The scenario of the interview consisted of three module in order to verify three hypotheses: 1. ‘hard’ rather than ‘soft’ competences are more important for a potential employer; 2. higher the organization’s development potential results in better assessment of working conditions by IT specialists; 3. better ratings of Polish economy was linked more positive personal predictions related to prospects of professional career. The article includes some recommendations on the design of a quantitative study of specialists in IT/cyber-security. Generally, the position of IT specialists on the Polish labour market seems to be well grounded in their skills and structural demand for their work in Poland’s financial sector.